Cellulose-based diaphragm as well as preparation method and application thereof

By preparing a cellulose-based separator with a suitable pore size structure and mechanical strength, the problem of the zinc negative electrode of an aqueous zinc ion battery is easily corroded, and the cycle stability and safety of the battery are improved.

CN119481564APending Publication Date: 2025-02-18QINGYUAN HUAYUAN INST OF SCI & TECH COLLABORATIVE INNOVATION CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411623917.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The negative electrode of the aqueous zinc ion battery is easily corroded, resulting in a degradation of battery performance and a shortening of cycle life. The mechanical properties of traditional diaphragm materials are poor, which can easily lead to battery short circuits.

Method used

By utilizing the interaction between nanocellulose and TEMPO after oxidation of cellulose-COO, a cellulose-based separator with a suitable pore size structure and a better mechanical strength is prepared, thereby improving the electrochemical stability of the zinc negative electrode.

Benefits of technology

It improves the cycle stability of the zinc negative electrode, extends the battery life, enhances the battery safety, inhibits the corrosion of the zinc negative electrode, and achieves better electrochemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481564A_ABST
    Figure CN119481564A_ABST
Patent Text Reader

Abstract

The invention discloses a cellulose-based diaphragm as well as a preparation method and application thereof, nano-crystalline cellulose and TEMPO oxidized nano-crystalline cellulose are dispersed and mixed, and then suction filtration and drying are performed to obtain the final cellulose-based zinc ion battery diaphragm. According to the preparation method of the cellulose-based zinc ion battery diaphragm provided by the invention, the cellulose diaphragm with a proper aperture structure and relatively small thickness is prepared by utilizing the interaction between nano cellulose hydroxyl (-OH) and cellulose-COO-oxidized by TEMPO, so that the cycling stability of a zinc negative electrode is improved, the corrosion of the zinc negative electrode is inhibited, and the service life of the battery is prolonged. The cellulose-based diaphragm has good mechanical strength, the zinc / potassium vanadate total battery assembled by the diaphragm shows good cycle stability, and with further research and development, the cellulose-based diaphragm is expected to play a greater role in the future battery technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and more specifically, to a cellulose-based diaphragm and a preparation method and application thereof. Background Art

[0002] As the global energy crisis and environmental pollution problems intensify, people are paying more and more attention to the shift from traditional, unsustainable fossil fuels to new, renewable clean energy. In order to effectively utilize these clean energy, it is particularly important to develop new electrochemical energy storage technologies with high performance, long cycle, high safety, economy and environmental friendliness. These technologies can not only improve energy conversion efficiency, but also ensure the durability and safety of energy use, while reducing the impact on the environment and promoting the goal of sustainable development. Aqueous zinc-ion batteries (ZIBs) are valued for their use of metallic zinc as the negative electrode material. This battery has many advantages, including high theoretical specific capacity (up to 820mAh / g), low redox potential (-0.76V relative to standard hydrogen electrode), abundant raw material resources, high stability in water and low production cost.

[0003] One of the core components of aqueous zinc-ion batteries is the diaphragm, which plays the role of isolating the positive and negative electrode materials and preventing short circuits in the battery, while allowing ions to pass through to ensure the normal operation of the battery. As a key component in zinc-ion batteries, the performance of the diaphragm directly affects the safety, cycle stability and energy efficiency of zinc-ion batteries. The negative zinc electrode of aqueous zinc-ion batteries is prone to corrosion, resulting in problems such as decreased performance and shortened cycle life of zinc-ion batteries. Traditional diaphragm materials, such as glass fiber diaphragms, are often used for zinc-ion battery diaphragms because they have a large pore structure that allows rapid transmission of electrolyte ions, but their mechanical properties are poor, and large pores can also cause dendrites to pierce and cause battery short circuits. Therefore, researchers are committed to developing new diaphragm materials to solve these problems. Cellulose is one of the most abundant organic polymers on earth. It is not only easy to degrade, but also has the characteristics of easy chemical modification and good biocompatibility. These characteristics make cellulose widely used in many industrial fields such as papermaking, textiles, food and medicine. Cellulose mainly exists in the cell walls of plants and certain algae, and can also be synthesized by microorganisms. These properties can be exploited to develop low-cost, high-performance cellulose-based separator materials that not only have excellent wettability but are also resistant to corrosion by chemical solvents and electrochemical environments.

[0004] Therefore, it is of great significance to develop a cellulose-based separator to improve the electrochemical stability of Zn anode. Summary of the invention

[0005] The purpose of the present invention is to provide a cellulose-based diaphragm and a preparation method and application thereof, to improve the electrochemical stability of the zinc negative electrode through the diaphragm structure and functional groups, and to utilize nanocellulose hydroxyl (-OH) and TEMPO-oxidized cellulose -COO - The interaction between them can produce a cellulose separator with suitable pore structure and good mechanical strength, which improves the cycle stability of the zinc negative electrode, and finally obtains ZIBs with good cycle stability.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a cellulose-based separator comprising at least one of nanocellulose and carboxylated nanocellulose.

[0008] Preferably, the cellulose-based separator contains nanocellulose and carboxylated nanocellulose in a mass ratio of (0.5-5):1.

[0009] More preferably, the mass ratio of the nanocellulose to the carboxylated nanocellulose is (1-4):1.

[0010] More preferably, the mass ratio of the nanocellulose to the carboxylated nanocellulose is 1:1.

[0011] In the present invention, the nanocellulose is the commonly used nanocellulose in the art, and its source includes but is not limited to at least one of wood pulp cellulose, bamboo pulp cellulose, cotton pulp cellulose, and hemp pulp cellulose, and it can be purchased through commercial channels or obtained by self-production.

[0012] Here, a homemade method for nanocellulose is provided as an example:

[0013] The preparation method of the nano cellulose comprises the following steps: evenly disintegrating a pulp sheet made of plant fiber as raw material, adding water to prepare a slurry, and then grinding and homogenizing the pulp to obtain the nano cellulose.

[0014] In the method for preparing nanocellulose, the pulp board using plant fiber as raw material includes but is not limited to bleached kraft softwood pulp board.

[0015] In the present invention, the carboxylated nanocellulose is the carboxylated nanocellulose commonly used in the art, which can be purchased through commercial channels or obtained by self-production.

[0016] Here, a homemade method for carboxylating nanocellulose is provided as an example:

[0017] The preparation method of the carboxylated nanocellulose comprises: performing an oxidation treatment on the nanocellulose by using a TEMPO oxidation method to obtain the carboxylated nanocellulose; specifically, the mixed solution of NaBr and TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) is added dropwise to the nanocellulose, and then a NaClO solution is added, and then an alkali solution is added to adjust the pH to 10 for reaction, so as to obtain the carboxylated nanocellulose.

[0018] In the method for preparing carboxylated nanocellulose, the reaction time is 8-10 hours.

[0019] In a second aspect, the present invention provides a method for preparing a cellulose-based diaphragm, comprising the following steps:

[0020] The cellulose solution is filtered to obtain a cellulose-based membrane;

[0021] The cellulose solution is at least one of a nanocellulose solution and a carboxylated nanocellulose solution.

[0022] Preferably, the mass fraction of the nanocellulose solution is 0.1-5wt.%.

[0023] Preferably, the mass fraction of the carboxylated nanocellulose solution is 0.1-5wt.%.

[0024] Preferably, the preparation method of the cellulose-based separator is specifically as follows:

[0025] Add water to the cellulose solution, disperse it, filter it, transfer the filter cake into tert-butyl alcohol, soak it, and dry it to obtain a cellulose-based diaphragm.

[0026] More preferably, the dispersion speed is 500-30000 rpm and the time is 0.2-30 min.

[0027] More preferably, the soaking time is 1-48h.

[0028] More preferably, the drying temperature is 30-150° C. and the drying time is 0.2-60 min.

[0029] Preferably, the preparation method of the nanocellulose solution is: evenly disintegrating the bleached kraft softwood pulp board, adding water to prepare a slurry, and then refining and homogenizing to obtain the nanocellulose solution.

[0030] More preferably, the refining rotation speed is 15000-25000 rpm, specifically 20000 rpm.

[0031] More preferably, the homogenization treatment is to use a nano homogenizer to first homogenize 3 times with a D12 nozzle at 17 MPa, and then homogenize 3 times with a D8 nozzle at 20 MPa.

[0032] Preferably, the preparation method of the carboxylated nanocellulose solution is: dropwise adding a mixed solution of NaBr and TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) into the nanocellulose solution, then adding NaClO solution, and then adding alkali solution to adjust the pH to 10 for reaction, thereby obtaining the carboxylated nanocellulose solution.

[0033] More preferably, the reaction time is 8-10 hours.

[0034] In a third aspect, the present invention provides a use of a cellulose-based separator in a battery.

[0035] Preferably, the battery is a zinc ion battery.

[0036] More preferably, the zinc ion battery is an aqueous zinc ion battery.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The cellulose-based diaphragm prepared by the present invention has excellent safety performance and can improve the electrochemical stability of the zinc negative electrode. Cellulose raw materials are green, environmentally friendly and renewable. It is a natural polymer material with good biodegradability, which means that batteries using cellulose-based diaphragms have less impact on the environment after their life cycle. The hydroxyl group (-OH) on cellulose and the -COO after TEMPO oxidation - The stability of zinc deposition is improved. The composite structure of the diaphragm has a good pore size distribution and a thin thickness. The zinc / potassium vanadate full battery assembled with the diaphragm shows good electrochemical stability. The cellulose-based diaphragm has good mechanical strength, which helps to improve the safety of the battery. The cellulose-based diaphragm also inhibits the corrosion of the zinc negative electrode to a certain extent. With further research and development, cellulose-based diaphragms are expected to play a greater role in future battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a scanning electron microscope image of the cellulose-based separator prepared in Example 1.

[0040] Figure 2 This is a scanning electron microscope image of the cellulose-based separator prepared in Example 2.

[0041] Figure 3 This is a scanning electron microscope image of the cellulose-based separator prepared in Example 3.

[0042] Figure 4 This is a scanning electron microscope image of the cellulose-based separator prepared in Example 4.

[0043] Figure 5 This is the Fourier infrared spectra of the cellulose-based membranes of Examples 1-3.

[0044] Figure 6 It is a bar graph of the thickness of the diaphragms of Examples 1-4 and Comparative Example 1.

[0045] Figure 7 The pore size distribution diagram of the diaphragm of Comparative Example 1 and Examples 3-4.

[0046] Figure 8 The mechanical tensile stress-strain curves of the diaphragms of Comparative Example 1 and Example 3 are shown.

[0047] Fig. 9 This is the performance diagram of the Zn / / Zn symmetric battery of the comparative example 1 separator.

[0048] Fig.10 This is the Zn / / Zn symmetric battery performance diagram of the cellulose-based membrane prepared in Example 3.

[0049] Fig.11 This is the Tafel curve of the diaphragm of Comparative Example 1.

[0050] Fig.12 This is the Tafel curve of the cellulose-based separator of Example 3.

[0051] Fig.13 This is a cycle performance diagram of a full battery prepared using the cellulose-based separator of Example 3. DETAILED DESCRIPTION

[0052] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0053] The experimental methods in the following examples without specifying specific conditions are generally carried out according to conventional conditions in the art or according to conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.

[0054] Example 1

[0055] This embodiment provides a cellulose-based separator, comprising nanocellulose;

[0056] The preparation method of the above-mentioned cellulose-based diaphragm comprises the following steps:

[0057] S1. 7 g of bleached kraft softwood pulp was evenly deflated, water was added to form a slurry, and then pulped at 20,000 rpm. The cellulose nanofiber slurry was homogenized 3 times with a D12 nozzle at 17 MPa and 3 times with a D8 nozzle at 20 MPa. Finally, the homogenized cellulose nanofiber slurry was diluted with water to a nanocellulose solution with a mass fraction of 0.7 wt.%, which was marked as CNF solution.

[0058] S2. Add 1000 mL of water to a nanocellulose solution (CNF solution) with a mass fraction of 0.7 wt.%, stir and disperse it with a high-speed disperser at 10,000 rpm for 1 min, pour it into a solvent filter for suction filtration, transfer the filter cake into tert-butanol and soak it for 3 h, place it in a hot press at 70°C and dry it for 3 min, and then use a punch to cut it into discs with a diameter of 16 mm to obtain a cellulose-based diaphragm, which can also be called a CNF diaphragm.

[0059] Example 2

[0060] This embodiment provides a cellulose-based separator, comprising carboxylated nanocellulose;

[0061] The preparation method of the above-mentioned cellulose-based diaphragm comprises the following steps:

[0062] S1. Add 0.1 g NaBr and 0.016 g TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) to 100 mL water, stir and mix to dissolve, obtain a mixed solution of NaBr and TEMPO (2,2,6,6-tetramethylpiperidinyl oxide), and add it dropwise to 500 mL of a nanocellulose solution (CNF solution, the preparation method of which is referred to Example 1) with a mass fraction of 1.3 wt.%, then add 150 mL of a 5 mol / L NaClO solution, then add 0.5 mol / L NaOH solution to adjust to pH = 10, stir and react for 8 h, and dilute it with water to a carboxylated nanocellulose solution with a mass fraction of 0.7 wt.%, marked as TONF solution;

[0063] S2. Add 1000 mL of water to a carboxylated nanocellulose solution (TONF solution) with a mass fraction of 0.7 wt.%, stir and disperse with a high-speed disperser at 20,000 rpm for 3 minutes, pour into a solvent filter for suction filtration, transfer the filter cake into tert-butanol and soak for 5 hours, place it in a hot press at 80°C and dry it for 3 minutes, and then use a punch to cut it into discs with a diameter of 16 mm to obtain a cellulose-based diaphragm, which can also be called a TONF diaphragm.

[0064] Example 3

[0065] This embodiment provides a cellulose-based separator comprising nanocellulose and carboxylated nanocellulose in a mass ratio of 1:1;

[0066] The preparation method of the above-mentioned cellulose-based diaphragm comprises the following steps:

[0067] S1. 7 g of bleached kraft softwood pulp was evenly deflated, water was added to form a slurry, and then pulped at 20,000 rpm, homogenized 3 times with a D12 nozzle at 17 MPa, and then homogenized 3 times with a D8 nozzle at 20 MPa, and then diluted with water to a nanocellulose solution with a mass fraction of 0.4 wt.%;

[0068] S2. Add 0.1 g NaBr and 0.016 g TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) to 100 mL water, stir and mix to dissolve, and obtain a mixed solution of NaBr and TEMPO (2,2,6,6-tetramethylpiperidinyl oxide), and add it dropwise to 500 mL of a nanocellulose solution having a mass fraction of 1.3 wt.%, and then add 150 mL of a 5 mol / L NaClO solution, and then add 0.5 mol / L NaOH solution to adjust to pH = 10, stir and react for 8 h, and then dilute it with water to a carboxylated nanocellulose solution having a mass fraction of 0.6 wt.%;

[0069] S3. Mix 90 mL of a 0.4 wt.% nanocellulose solution and 60 mL of a 0.6 wt.% carboxylated nanocellulose solution, add 1000 mL of water, stir and disperse with a high-speed disperser at 15,000 rpm for 2 min, pour into a solvent filter for suction filtration, transfer the filter cake into tert-butyl alcohol and soak for 6 h, place it in a hot press at 90 ° C and dry it for 10 min, and then use a punch to cut it into a disc with a diameter of 16 mm to obtain a cellulose-based diaphragm;

[0070] In step S3, the mass ratio of the nanocellulose to the carboxylated nanocellulose is 1:1.

[0071] Example 4

[0072] This embodiment provides a cellulose-based separator comprising nanocellulose and carboxylated nanocellulose in a mass ratio of 4:1;

[0073] The preparation method of the above-mentioned cellulose-based diaphragm comprises the following steps:

[0074] S1. 7 g of bleached kraft softwood pulp was evenly deflated, water was added to form a slurry, and then pulped at 20,000 rpm, homogenized 3 times with a D12 nozzle at 17 MPa, and then homogenized 3 times with a D8 nozzle at 20 MPa, and then diluted with water to a nanocellulose solution with a mass fraction of 0.6 wt.%;

[0075] S2. Add 0.1 g NaBr and 0.016 g TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) to 100 mL water, stir and mix to dissolve, and obtain a mixed solution of NaBr and TEMPO (2,2,6,6-tetramethylpiperidinyl oxide), and add it dropwise to 500 mL of a nanocellulose solution having a mass fraction of 1.3 wt.%, and then add 150 mL of a 5 mol / L NaClO solution, and then add 0.5 mol / L NaOH solution to adjust to pH = 10, stir and react for 8 h, and then dilute it with water to a carboxylated nanocellulose solution having a mass fraction of 0.4 wt.%;

[0076] S3. Mix 80 mL of a 0.6 wt.% nanocellulose solution and 30 mL of a 0.4 wt.% carboxylated nanocellulose solution, add 1000 mL of water, stir and disperse with a high-speed disperser at 15,000 rpm for 2 min, pour into a solvent filter for suction filtration, transfer the filter cake into tert-butyl alcohol and soak for 6 h, place it in a hot press at 90 ° C and dry it for 30 min, and then use a punch to press and cut it into a disc with a diameter of 16 mm to obtain a cellulose-based diaphragm;

[0077] In step S3, the mass ratio of the nanocellulose to the carboxylated nanocellulose is 4:1.

[0078] Comparative Example 1

[0079] This comparative example provides a commercial glass fiber separator.

[0080] Sample characterization

[0081] Figure 1 This is a scanning electron microscope image of the cellulose-based separator prepared in Example 1. Figure 2 This is a scanning electron microscope image of the cellulose-based separator prepared in Example 2. Figure 3 This is a scanning electron microscope image of the cellulose-based separator prepared in Example 3. Figure 4 This is a scanning electron microscope image of the cellulose-based separator prepared in Example 4.

[0082] Depend on Figure 1-4 It can be seen that Example 1 has an obvious fibrous structure, and the separator is a three-dimensional structure composed of interlaced fibers, and obvious pores can be seen. After oxidation, the separator of Example 2 is very dense and has no obvious fibrous structure. This shows that after the introduction of carboxyl groups through oxidation, the interaction between cellulose chains is enhanced. Figure 3 Figure 4The scanning images of the diaphragm obtained by mixing nanocellulose (CNF) and carboxylated nanocellulose (TONF) in different proportions. It can be seen from the figure that when the CNF:TONF mass ratio is relatively large, the diaphragm structure shows an obvious fiber structure, and when the TONF content increases, the diaphragm structure becomes denser.

[0083] Figure 5 The Fourier transform infrared spectra of the cellulose-based membranes of Examples 1-3 are shown in FIG. Figure 5 It can be seen that nanocellulose contains hydrophilic groups hydroxyl -OH, which are introduced into -COO by TEMPO oxidation. - After the groups were obtained, carboxylated nanocellulose was obtained. Example 3 simultaneously showed -OH and -COO groups because it contained both nanocellulose and carboxylated nanocellulose.

[0084] Figure 6 The thickness bar graph of the diaphragm of Examples 1-4 and Comparative Example 1. Figure 6 It can be seen that the thickness of the cellulose-based membranes in Examples 1-4 are 50 μm, 30 μm, 34 μm, and 40 μm, respectively, and the thickness of the cellulose-based membrane in Comparative Example 1 is 260 μm. It can be seen that the cellulose-based membranes in Examples 1-4 of the present invention have a thinner thickness, and a thinner thickness is beneficial to saving space in aqueous zinc-ion batteries and increasing the volumetric specific energy of aqueous zinc-ion batteries. Figure 7 The pore size distribution diagram of the diaphragm of Comparative Example 1 and Examples 3-4. Figure 7 It can be seen that the cellulose separator of Example 3 has a relatively uniform pore size distribution, and the pore size is nanometer scale. Figure 8 The mechanical tensile stress-strain curves of the diaphragms of Comparative Example 1 and Example 3 are shown in FIG. Figure 8 It can be seen that the tensile stress of Example 3 is 54 MPa, which is much greater than the tensile stress (0.5 MPa) of the diaphragm of Comparative Example 1, indicating that Example 3 has better mechanical properties.

[0085] Performance Testing

[0086] 1. A Zn / / Zn symmetrical battery was prepared using the cellulose-based separator of Example 3 and the separator of Comparative Example 1. In the Zn / / Zn symmetrical battery, both the positive and negative electrodes were zinc foils, and the electrolyte was a 2 mol / L ZnSO4 solution. In the full battery, the negative electrode material was zinc foil; the positive electrode sheet was made of the positive electrode active material K2V8O 21 , conductive agent Ketjen black, and binder (PVDF) are dissolved in NMP solvent in a mass ratio of 7:2:1, and then coated on stainless steel foil and dried; the electrolyte is 2 mol / L ZnSO4 solution.

[0087] Fig. 9 This is the performance diagram of the Zn / / Zn symmetric battery of the comparative example 1 separator. Fig.10This is the Zn / / Zn symmetric battery performance diagram of the cellulose-based membrane prepared in Example 3.

[0088] Fig. 9 , 10 The Zn / / Zn symmetric battery assembled with the separators of Comparative Example 1 and Example 3 was -2 、2mAhcm -2 From the performance, it can be seen that compared with the commercial glass fiber separator in Comparative Example 1, the cellulose-based separator in Example 3 exhibits better zinc deposition stability and improves the electrochemical stability of the zinc negative electrode.

[0089] Fig.11 This is the Tafel curve of the diaphragm of Comparative Example 1. Fig.12 This is the Tafel curve of the cellulose-based separator of Example 3.

[0090] from Figure 11-12 It can be seen that the corrosion current of the membrane battery in comparative example 1 is 7.24 mA cm -2 , the corrosion current of Example 3 is reduced to 0.79 mA cm -2 , indicating that the cellulose-based separator effectively inhibited the corrosion of the zinc electrode.

[0091] 2. The full battery performance test of the cellulose-based separator of Example 3 is carried out as follows:

[0092] (1) Preparation of positive electrode sheet: positive electrode active material K2V8O 21 , a conductive agent Ketjen black, and a binder (PVDF) are dissolved in NMP in a mass ratio of 7:2:1, and then coated on a stainless steel foil and dried to obtain a positive electrode sheet;

[0093] (2) A full battery was assembled using a metal zinc sheet as the negative electrode of the battery, the positive electrode sheet prepared in step (1) as the positive electrode, the cellulose-based diaphragm of Example 1 as the diaphragm, and a 2M ZnSO4 solution as the electrolyte. The cycle performance of the full battery was then tested using a NEWARE electrochemical test system at a current density of 3 A / g. The experimental results are shown in FIG. Fig.13 shown.

[0094] Fig.13 The cycle performance diagram of the full battery prepared using the cellulose-based separator of Example 3. Fig.13 It can be seen that the full battery prepared using the cellulose-based separator of Example 3 has good cycle stability at a current density of 3 A / g.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A cellulose-based separator, characterized in that Contains at least one of nanocellulose and carboxylated nanocellulose.

2. The cellulose-based separator according to claim 1, characterized in that The cellulose-based separator contains nanocellulose and carboxylated nanocellulose in a mass ratio of (0.5-5):

1.

3. The cellulose-based separator according to claim 1, characterized in that The preparation method of the carboxylated nanocellulose is: oxidizing the nanocellulose by using the TEMPO oxidation method to obtain the carboxylated nanocellulose.

4. The cellulose-based separator according to claim 3, characterized in that The preparation method of the carboxylated nanocellulose is specifically as follows: a mixed solution of NaBr and 2,2,6,6-tetramethylpiperidinyl oxide is added dropwise into the nanocellulose, a NaClO solution is added, and then an alkali solution is added to adjust the pH to 10 for reaction, thereby obtaining the carboxylated nanocellulose.

5. A method for preparing the cellulose-based separator according to any one of claims 1 to 4, characterized in that: The steps include: The cellulose solution is filtered to obtain a cellulose-based membrane; The cellulose solution is at least one of a nanocellulose solution and a carboxylated nanocellulose solution.

6. The method for preparing a cellulose-based diaphragm according to claim 5, characterized in that: The mass fraction of the nanocellulose solution is 0.1-5wt.%.

7. The method for preparing a cellulose-based diaphragm according to claim 5, characterized in that: The mass fraction of the carboxylated nanocellulose solution is 0.1-5 wt.%.

8. The method for preparing a cellulose-based diaphragm according to claim 5, characterized in that: The preparation method of the cellulose-based diaphragm is specifically as follows: Add water to the cellulose solution, disperse it, filter it, transfer the filter cake into tert-butyl alcohol, soak it, and dry it to obtain a cellulose-based diaphragm.

9. The method for preparing a cellulose-based diaphragm according to claim 8, characterized in that: Including at least one of the following (1)-(3): (1) The dispersion speed is 500-30000 rpm and the time is 0.2-30 min; (2) The soaking time is 1-48 hours; (3) The drying temperature is 30-150°C and the drying time is 0.2-60 min.

10. Use of the cellulose-based separator according to any one of claims 1 to 4 in a battery.

Citation Information

Cited By

  • Zinc negative electrode-diaphragm integrated structure containing dynamic self-adaptive protection and preparation method of zinc negative electrode-diaphragm integrated structure

    CN122118126A